Extracellular vescicles in psoriasis: from pathogenesis to possible roles in therapy - Iuliano, Marco; Grimaldi, Lorenzo; Rosa, Paolo; Scibetta, Sofia; Bernardini, Nicoletta; Proietti, Ilaria; Tolino, Ersilia; Skroza, Nevena; Potenza, Concetta; Mangino, Giorgio; Romeo, Giovanna (Frontiers in Immunology, 2024)
Psoriasis is a chronic inflammatory disease affecting skin and joints characterized by a chronically altered immune and inflammatory response. Several factors occur from the onset to the development of this disease due to different types of cells spatially and temporally localized in the affected area, such as, keratinocytes, macrophages, neutrophils and T helper lymphocytes. This scenario leads to the chronic release of high levels of inflammatory mediators (i.e., IL-17, IL-23, IL-22, TNF-, S100 proteins, Defensins) and lastly parakeratosis and thickening of the stratum spinosum. Extracellular vesicles (EVs) are small double membraned biological nanoparticles that are secreted by all cell types and classified, based on dimension and biogenesis, into exosomes, microvesicles and apoptotic bodies. Their role as vessels for long range molecular signals renders them key elements in the pathogenesis of psoriasis, as well as innovative platforms for potential biomarker discovery and delivery of fine-tuned anti-inflammatory therapies. In this review, the role of EVs in the pathogenesis of psoriasis and the modulation of cellular microenvironment has been summarized. The biotechnological implementation of EVs for therapy and research for new biomarkers has been also discussed.